Paramecium calcium channels are blocked by a family of calmodulin antagonists. - Ehrlich, B E (1988)
Although the voltage-sensitive Ca channel present in Paramecium has been subjected to detailed physiological and genetic analysis, no organic ligands have been described that block this channel with high affinity and that ultimately can be used to identify channel components. Based on a previous observation that the naphthalene sulfonamide calmodulin antagonist W-7 can block Paramecium Ca channels at high concentration, we have synthesized analogs of W-7 that block these channels at concentrations of less than 1 microM. The effectiveness of these compounds was tested both by a sensitive behavioral assay and on Ca channels that had been incorporated into planar lipid bilayers. Despite the fact that these compounds are effective Paramecium calmodulin antagonists, two independent lines of evidence suggest that W-7 and its analogs block the Ca channel by a mechanism that is independent of their action on calmodulin. In addition, the sensitivity to W-7 or dihydropyridines of Ca channels present in a number of eukaryotic phyla has been used to identify similarities in Ca channels from widely diverse organisms. It appears that the pharmacological specificity provides a means to group Ca channels.